Family Experience With Pierre Robin Sequence: A Qualitative Study. (June 2020) - Skirko, Jonathan R.; Pollard, Sarah Hatch; Slager, Stacey; Hung, Man; Weir, Charlene
Objective: To identify concepts and constructs important to parents of children with Pierre Robin Sequence (PRS). Design: Qualitative study. Setting: All children received some care at a tertiary hospital with additional care at outside facilities. Interviews were conducted in nonclinical locations, including remote locations. Participants: Parents of children <5 years old with a diagnosis of PRS. Prior treatments included observation, positioning, nasal trumpet, mandibular distraction osteogenesis, tracheostomy, and gastrostomy. Intervention: Semi-structured interviews with individuals (4) and with groups (focus groups, 4) were conducted using open-ended questions and non-leading prompts. Transcripts were analyzed with iterative open and axial coding. Concepts and constructs were identified and refined into codes and central themes. Interviews were conducted until thematic saturation was achieved. Results: Sixteen parents were interviewed. Their experiences were coded into 5 main themes, which can be summarized as: (1) child's symptoms/well-being, (2) parents' grief/isolation, (3) family stress, (4) relationships with providers, and (5) psychological and technical growth. Difficulty with feeding, weight gain, and breathing problems were core physical issues described by participants with associated intense fear. Participants described frustration from not only lack of care coordination, slow diagnoses, and poor communication but also gratitude for providers who served as advocates. Participants described gradual development of knowledge/competencies. Conclusions: Families of children with PRS have experiences that profoundly affect their lives. Child's physical symptoms/well-being and parents' psychosocial well-being provide content for a future PRS-specific quality-of-life instrument. Concepts that emerged also provide a framework to improve parents' experience and enhance their children's quality of care.